The Use of Edmodo As A Social Media to Support The Enhancement of Students Paragraph Writing Skills on The Students of First Semester of STKIP Pancasakti Tangerang - Ramdhani, Akhmad Subkhi (LPPM Universitas Mohammad Husni Thamrin, 2017)
Writing a paragraph academically is not an easy task; it consists of lengthy procedures and the ability to write skilfully. In addition, writing a paragraph academically is very important in academic life. However, in reality, many of the difficulties of writing a paragraph academically seen and have been proven by the students’ writing test. This research is aimed to explore the use of Edmodo as a media to enhance students’ paragraph writing skills to promote the extensive learning at STKIP Pancasakti Tangerang. The method used in this research is qualitative approach, and it applied Research and Development technique. In this case, the writer collected the data by using observation, structural interview, questionnaire and documentation. The interview was done for the students of first semester at STKIP Pancasakti Tangerang. Based on the result of the research, it was found that there were several factors which influence students’ inabilities to write an academic paragraph properly, they were students’ writing ability was low or poor, time limitation, uncomfortable feeling in learning English, lack of motivation, lack of exposures, insufficient materials, and did not know how to start writing lack of feedback. In addition, it was also found that Edmodo had some features that could be used to solve those problems of the research, the problems of students in writing a paragraph academically. This research can be concluded that the use of Edmodo as a media to enhance students’ paragraph writing skills to promote the extensive learning at STKIP Pancasakti Tangerang is useful. It is proven by several problems that hinder the teaching learning process are solved.